[zu:] Martin Kagel, David Z. Saltz (Ed.): Open Wounds: Holocaust Theater and the Le-gacy of George Tabori. - Eke, Norbert

Kunst, Literatur und Kultur des frühen 19. Jahrhunderts - Eke, Norbert Otto (Kunst, Literatur und Kultur des frühen 19. Jahrhunderts | Die Revolution von 1848/49)

Large eddy simulation of iron oxide formation in a laboratory spray flame (Applications in Energy and Combustion Science)
Iron oxide nanoparticles are very interesting for many applications in different industrial sectors. A promising process to manufacture these nanoparticles is flame spray pyrolysis (FSP). A lack of understanding of the individual sub-processes in FSP makes it challenging to tailor nanoparticle properties. This work provides insights into the formation of iron oxide nanoparticles in a turbulent spray flame using Large Eddy Simulations (LES), which are based on a comprehensive model, including customized submodels. Highlights are the adaption of a turbulent combustion model and a bivariate hybrid method of moments for modeling nanoparticle dynamics. The work focuses on the SpraySyn burner, which is a standardized laboratory burner and was operated with a precursor-solvent mixture of ethanol and iron(III) nitrate nonahydrate. For studying the relevance of precursor chemistry, LES using an evaporation-limited precursor chemistry model is compared with a model that includes detailed iron chemistry. A further novelty is the inclusion of adsorption in the simulation, which defines a third model for comparison. Sufficient validation is achieved for the undoped LES using experimental data from the literature. A strong impact of the detailed iron chemistry and adsorption is found on the precursor consumption and the aggregate and primary particle formation. Comparing the particle diameters with experimental measurements from the literature and data generated for this work is found unsuitable to asses the precursor chemistry model and revealed an urgent need for future experimental and numerical research. This work serves as a step forward in realizing a reliable model.
Keywords: Flame spray pyrolysis; Iron oxide formation; Large eddy simulation; Method of moments; SpraySyn

Der ‚gelungene Satz‘. Laudatio zur Verleihung des Thomas-Valentin-Literaturpreises der Stadt Lippstadt an Christoph Peters - Eke, Norbert Otto (Literatur in Westfalen. Beiträge zur Forschung 19)

Nanoparticle Concentration Measurement in Flame Spray Pyrolysis (Poster) - Massopo, Orlando; Schmid, Hans-Joachim; Gonchikzhapov, Munko; Kasper, Tina
Keywords: Absolute particle concentration; Flame Spray Pyrolysis; SMPS; Mass Spectrometry

Thomas Bernhard: Language, History, Subjectivity - Krylova, Katya; Schonfield, Ernest (Amsterdamer Beiträge zur neueren Germanistik)

A multiobjective continuation method to compute the regularization path of deep neural networks - Amakor, Augustina Chidinma; Sonntag, Konstantin; Peitz, Sebastian (arXiv)
Sparsity is a highly desired feature in deep neural networks (DNNs) since it ensures numerical efficiency, improves the interpretability of models (due to the smaller number of relevant features), and robustness. In machine learning approaches based on linear models, it is well known that there exists a connecting path between the sparsest solution in terms of the $\ell^1$ norm,i.e., zero weights and the non-regularized solution, which is called the regularization path. Very recently, there was a first attempt to extend the concept of regularization paths to DNNs by means of treating the empirical loss and sparsity ($\ell^1$ norm) as two conflicting criteria and solving the resulting multiobjective optimization problem. However, due to the non-smoothness of the $\ell^1$ norm and the high number of parameters, this approach is not very efficient from a computational perspective. To overcome this limitation, we present an algorithm that allows for the approximation of the entire Pareto front for the above-mentioned objectives in a very efficient manner. We present numerical examples using both deterministic and stochastic gradients. We furthermore demonstrate that knowledge of the regularization path allows for a well-generalizing network parametrization.

Error analysis of kernel EDMD for prediction and control in the Koopman framework - Philipp, Friedrich; Schaller, Manuel; Worthmann, Karl; Peitz, Sebastian; Nüske, Feliks (arXiv:2312.10460)
Extended Dynamic Mode Decomposition (EDMD) is a popular data-driven method to approximate the Koopman operator for deterministic and stochastic (control) systems. This operator is linear and encompasses full information on the (expected stochastic) dynamics. In this paper, we analyze a kernel-based EDMD algorithm, known as kEDMD, where the dictionary consists of the canonical kernel features at the data points. The latter are acquired by i.i.d. samples from a user-defined and application-driven distribution on a compact set. We prove bounds on the prediction error of the kEDMD estimator when sampling from this (not necessarily ergodic) distribution. The error analysis is further extended to control-affine systems, where the considered invariance of the Reproducing Kernel Hilbert Space is significantly less restrictive in comparison to invariance assumptions on an a-priori chosen dictionary.

Umfrage: Tax Compliance und Verrechnungspreise - Greil, Stefan; Kaluza-Thiesen, Eleonore; Schulz, Kim Alina; Sureth-Sloane, Caren

Essen und Ernährung im Sachunterricht - Bigga, Regine (HiBiFo – Haushalt in Bildung & Forschung)
Ernährungsbildung ist derzeit nur unzureichend in der Primarstufe verankert, sie sollte es jedoch sein, damit Kinder Kompetenzen für die Alltagsbewältigung im Handlungsfeld Ernährung und somit zur Teilhabe an der Gesellschaft anbahnen können. Essen und Ernährung bieten sich als perspektivenvernetzender Themenbereich für den Sachunterricht an.
Keywords: Ernährungsbildung; Sachunterricht; Curriculumentwicklung; Esskultur

Electrode Potential-Dependent Studies of Protein Adsorption on Ti6Al4V Alloy - Duderija, Belma; González-Orive, Alejandro; Ebbert, Christoph; Neßlinger, Vanessa; Keller, Adrian; Grundmeier, Guido (Molecules)
This article presents the potential-dependent adsorption of two proteins, bovine serum albumin (BSA) and lysozyme (LYZ), on Ti6Al4V alloy at pH 7.4 and 37 °C. The adsorption process was studied on an electropolished alloy under cathodic and anodic overpotentials, compared to the open circuit potential (OCP). To analyze the adsorption process, various complementary interface analytical techniques were employed, including PM-IRRAS (polarization-modulation infrared reflection-absorption spectroscopy), AFM (atomic force microscopy), XPS (X-ray photoelectron spectroscopy), and E-QCM (electrochemical quartz crystal microbalance) measurements. The polarization experiments were conducted within a potential range where charging of the electric double layer dominates, and Faradaic currents can be disregarded. The findings highlight the significant influence of the interfacial charge distribution on the adsorption of BSA and LYZ onto the alloy surface. Furthermore, electrochemical analysis of the protein layers formed under applied overpotentials demonstrated improved corrosion protection properties. These studies provide valuable insights into protein adsorption on titanium alloys under physiological conditions, characterized by varying potentials of the passive alloy.
Keywords: Chemistry (miscellaneous); Analytical Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Molecular Medicine; Drug Discovery; Pharmaceutical Science

Electropolymerization of acrylic acid on steel for enhanced joining by plastic deformation - Duderija, B.; Sahin, F.; Meinderink, D.; Calderón-Gómez, J.C.; Schmidt, H.C.; Homberg, W.; Grundmeier, G.; González-Orive, A. (Journal of Advanced Joining Processes)
Keywords: Mechanical Engineering; Mechanics of Materials; Engineering (miscellaneous); Chemical Engineering (miscellaneous)

„Fotos, die jede*r kennt?“ Eine empirische Untersuchung historischer Kenntnisforschung anhand von Bildikonen bei Studierenden des Lehramts Geschichte - Meyer-Hamme, Johannes; Fastlabend-Vargas, Daniel (Geschichtsdidaktisch intervenieren)

Fallbezogene Reflexionen von Haltung und Professionalisierung pädagogischer Akteur*innen im Kontext begabungs- und leistungsfördernder Schulentwicklung - Friedberger, Vanessa; Kaiser, Michaela; Kottmann, Brigitte; Schwermann, Anna (Potenziale erkennen - Talente entwickeln - Bildung nachhaltig gestalten. Beiträge aus der Begabungsforschung)

Absence of principal eigenvalues for higher rank locally symmetric spaces - Weich, Tobias; Wolf, Lasse Lennart (Communications in Mathematical Physics)
Given a geometrically finite hyperbolic surface of infinite volume it is a classical result of Patterson that the positive Laplace-Beltrami operator has no $L^2$-eigenvalues $≥ 1/4$. In this article we prove a generalization of this result for the joint $L^2$-eigenvalues of the algebra of commuting differential operators on Riemannian locally symmetric spaces $Γ\backslash G/K$ of higher rank. We derive dynamical assumptions on the $Γ$-action on the geodesic and the Satake compactifications which imply the absence of the corresponding principal eigenvalues. A large class of examples fulfilling these assumptions are the non-compact quotients by Anosov subgroups.

Geschichtstheorie im Geschichtsunterricht - Meyer-Hamme, Johannes (Geschichtsdidaktik)

Dynamics-induced charge transfer in semiconducting conjugated polymers - Bauch, Fabian; Dong, Chuan-Ding; Schumacher, Stefan (Journal of Materials Chemistry C)
Dynamics-induced interchain charge transfer in a polymer aggregate in stack configuration can be understood by single-oligomer polaron energy.
Keywords: Materials Chemistry; General Chemistry

Multi-Technology Cooperative Driving: An Analysis Based on PLEXE - Segata, Michele; Lo Cigno, Renato; Hardes, Tobias; Heinovski, Julian; Schettler, Max; Bloessl, Bastian; Sommer, Christoph; Dressler, Falko (IEEE Transactions on Mobile Computing)
Cooperative Driving requires ultra-reliable communications, and it is now clear that no single technology will ever be able to satisfy such stringent requirements, if only because active jamming can kill (almost) any wireless technology. Cooperative driving with multiple communication technologies which complement each other opens new spaces for research and development, but also poses several challenges. The work we present tackles the fallback and recovery mechanisms that the longitudinal controlling system of a platoon of vehicles can implement as a distributed system with multiple communication interfaces. We present a protocol and procedure to correctly compute the safe transition between different controlling algorithms, down to autonomous (or manual) driving when no communication is possible. To empower the study, we also develop a new version of PLEXE, which is an integral part of this contribution as the only Open Source, free simulation tool that enables the study of such systems with a modular approach, and that we deem offers the community the possibility of boosting research in this field. The results we present demonstrate the feasibility of safe fallback, but also highlight that such complex systems require careful design choices, as naïve approaches can lead to instabilities or even collisions, and that such design can only be done with appropriate in-silico experiments.

Improving Platooning Safety with Full Duplex Relaying and Beamforming - Hardes, Tobias; Klingler, Florian; Sommer, Christoph (IEEE Wireless Communications and Networking Conference 2023 (WCNC 2023))
Platooning is a promising application in the field of vehicular networks. It has the potential to improve traffic flow, but also road safety. However, unreliable communication has strong negative effects on platoon stability and, thus, safety on roads. To improve reliability, in this work, we propose using multi-hop communication for platooning using the Decode and Forward (DF) Full-Duplex Relaying (FDR) scheme together with beamforming. We use computer simulations to demonstrate that FDR latency has no observable negative effect on string stability or safety even while performing an emergency brake. We further show that this combined approach reaches a constant Packet Delivery Ratio (PDR) of 100 % even in situations with high interference and/or congestion, where traditional approaches fail.

Opportunistic Airborne Virtual Network Infrastructure for Urban Wireless Networks - Hardes, Tobias; Sommer, Christoph (Elsevier Computer Communications)
We study the suitability of Unmanned Aerial Vehicles (UAVs) as purely opportunistic airborne virtual network infrastructure to support urban wireless networks, specifically in two Vehicle-to-Everything (V2X) use cases: First, UAVs being used as relays for cooperative awareness applications; second, UAVs being used to coordinate channel access for platooning in urban areas. We do not require that these UAVs alter trajectory nor speed from those of their random, unrelated primary missions, so that these additional tasks can be executed with close-to-zero impact on the execution of their primary missions. Based on extensive computer simulations we show that, within a wide band of acceptable speeds, flight routes (up to a standard deviation of 300 m from the optimum) as well as altitudes, opportunistic relaying of transmissions via UAVs can yield a benefit to system performance that is on the same order of magnitude as that of optimally deployed UAVs. We further show that an opportunistic channel access control can reduce the total number of packet collisions by approx. 86 % compared to a scenario without any UAVs. Moreover, much of the reduction in impact due to suboptimal missions can be recovered simply by moderately increasing the number of UAVs.